UNION FOR THE LIBERATION OF UKRAINE AS A MODEL OF THE UKRAINIAN-CENTRIC ORGANIZATION (peer-review on the monograph: Pater Ivan. Union for the Liberation of Ukraine (1914-1918). Personalities / NAS of Ukraine, I. Krypiakevych Institute of Ukrainian Studies. Lviv, 2024. 404 p.) - IVANYSHYN, Petro; ROZLUTSKY, Ihor (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
peer-review on the monograph: Pater Ivan. Union for the Liberation of Ukraine (1914-1918). Personalities / NAS of Ukraine, I. Krypiakevych Institute of Ukrainian Studies. Lviv, 2024. 404 p.